Recovery: Restoration and regeneration as essential components within training programs - Calder, A. (American Swimming Magazine, 1997)
On the necessity and benefits of structured recovery periods both in terms of improved performances and decreased injury rates. On overtraining symptoms, methods for recovery, work/rest ratios, nutrition, physical therapy, psycho-regulatory training and planning recovery for competition.